Pengaruh Tax Avoidance dan Leverage terhadap Nilai Perusahaan Sektor Consumer Non Cyclicals yang terdaftar di Bursa Efek Indonesia Periode Tahun 2022-2024 - Suci Anggun Febianti; Ratnaningrum Ratnaningrum; Zahra Dinul Khaq; Febryantahanuji Febryantahanuji (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of Tax Avoidance and Leverage on Firm Value in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. Employing a quantitave approach, secondary data were gathered form annual financial statements on the official IDX website. Purposive sampling was utilized, yielding a final sample of 20 companies (60 total observations). Data analysis was performed using multiple linear regression, classicall assumption tests, and hypothesis testing, specifically the T-test and F-test. The empirical results demonstrate that, partially, tax avoidance does not significantly effect firm value ( P = l0.574 > 0.05 ). Similary, leverage exhibits no significant partial effect on firm value. Simultaneously, tax avoidance and leverage do not significants influence the firm value of consumer non-cyclicals companies, showing a low coefficient of determination. Furthermore, these independent variabels are proven to be unable to predict any changes in market valuation. These fidings imply that market valuation in this sector is driven predominantly by external factor or broader operational performance rather than tax management Consequently, managements should prioritize enhancing fundamental operational value over tax minimization or debt scaling.